Benin : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This report describes economic developments in Benin during the 1990s. During 1993-95, the reform strategy was further reinforced in the framework of a program supported under the enhanced structural adjustment facility; it included additional improvements in tax administration and tax reforms, a reallocation of government expenditures toward the priority social sectors, and continued restructuring of the public enterprise sector. Public finances improved further, with the government reducing its indebtedness to the Central Bank by about two-thirds, while public investment rose considerably, mostly to improve infrastructure and social services.